Perancangan mekanisme rel torch plasma cutting 1 (satu) Axis - I Wayan Suma Wibawa; I Komang Kantun; I Ketut Suherman; Risa Nurin Baiti; I Wayan Suirya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Plasma cutting is a method of cutting metal, especially steel, with relatively low cost and effectiveness, with satisfactory results. Where in the cut, it is enough to need a plasma cutting machine/inverter that is quite affordable, widely available in the market, and simple tools, an air compressor (no special oxygen/gas needed as in gas/oxygen and acetylene/LPG cutting), a power source, the material being cut and the cutting process can be carried out. How to use plasma cutting is relatively easy, namely by setting the machine and then directing the plasma torch to the cutting plane as needed by maintaining a stable movement and height. However, when we make repeated cuts, our concentration and physical strength will automatically decrease, so we need a tool that can help us direct/adjust the plasma torch, which is called a plasma cutting mechanism. After paying attention to these needs, a plasma cutting mechanism was designed with a working space/cutting length of 1200 mm, with a tool size of 1400 mm x 300mm x 200 mm length, width and height, estimated cost of Rp. 3,050,000,-, with a cutting speed setting of 100 mm/minute to 1000 mm/minute, a cutting height of 0 to 10 mm with an angle of 0 degree to 90 degree.